New forms of partnership: the role of logistics clusters in facilitating horizontal collaboration mechanisms (2019)
Although the benefits of horizontal collaboration have been well documented in the literature, research has yet to offer a detailed understanding of the mechanisms that firms employ to create successful horizontal collaboration. Further, the role of logistics clusters in facilitating horizontal collaboration is crucial but not clear yet. This paper addresses these gaps. In order to address the research objectives, we employ a systematic literature review methodology. As a result of this process, one hundred thirty-three (133) papers published in leading academic journals were systematically analyzed. These studies are reviewed under the theoretical lenses of the transaction cost economics (TCE) and the derived identification of governance mechanisms (i.e. joint value propositions, informal governance, formal governance and information exchange) to achieve successful horizontal collaboration. Further, we provide a detailed description of how logistics clusters can facilitate and promote the development of such mechanisms, illustrated with companies’ best practices. As a result, several testable research propositions are put forth. © 2019, © 2019 Informa UK Limited, trading as Taylor and Francis Group.